Environmental governance for sustainable development South Asian perspectives - Nabhi, Uma (Routledge, 2023)
This book studies the role of the United Nations Environment Programme (UNEP) as an advocate for greater environmental responsibility and analyses the major achievements and outcomes of two landmark conferences – Stockholm (1972) and Rio (1992) – which set the agenda for the future role of the UNEP. It discusses the UNEP’s evolution, objectives and the problems of differing perspectives within, its ability to deal with environmental challenges, its skill in successfully carrying out the mandate and contributing to the pursuit of environmental security.